Vous avez dit « révolution verte » ? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Le Dr H. Breman, directeur du Centre international pour la gestion de la fertilité des sols (IFDC-Afrique), au Togo, réagit